STRATEGIC MANAGEMENT OF THE ECONOMIC SECURITY OF THE AGRICULTURAL ENTERPRISE IN THE BUSINESS ENVIRONMENT - OLIINYK, Alina; ISHCHEIKIN, Tymur; KARTASHOV, Rostyslav; NEVKRYTYI, Mykhailo (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the main components of economic security. It has been proven that the main goal of the economic security of agricultural enterprises is to ensure their stability and long-term development under conditions of market competition. It is noted that an important element of the company's security system is its management mechanism, which ensures the achievement of security goals and the resolution of set tasks. The economic security management mechanism of the enterprise includes a set of elements such as the philosophy of economic security of the enterprise; functions implementing the economic security management process; resource provision of the mechanism; target orientation, containing the main organizational forms and economic tools necessary to ensure the economic security of the enterprise's functioning. Ensuring the financial component of economic security involves avoiding such factors as tax evasion, non-payment of taxes due to loss of liquidity, violation of cash and payment discipline, unsatisfactory state of settlements with counterparties. The internal control of the economic security of the enterprise involves the implementation of the process of obtaining objective, qualitative and quantitative assessments of the current state of the economic security of the enterprise in accordance with certain criteria and security indicators. For this purpose, it is necessary to use control measures at the enterprise, which will allow checking the degree of compliance with the economic security of the enterprise. The results of security control make it possible to build an accounting information protection system that is optimal from the point of view of efficiency and costs, adequate to the current tasks and goals of business activity. In the modern conditions of conducting agrarian business, there is a need to strengthen measures to support the economic security of agricultural enterprises, which is due to the high risk of activity and the instability of their functioning. Observance of economic security, constant monitoring of key factors of its influence and sources of threats, development of preventive measures for their neutralization and minimization will ensure the reliability of subjects of agrarian entrepreneurship and their sustainable development in the future.
Keywords: strategic management; economic security; agricultural enterprises; business environment; long-term development